Dear Ms. Schubert - Lipska, Ewa 1945- (Princeton University Press, 2021)
The first complete English translation of Ewa Lipska's exciting "Dear Ms. Schubert" poemsEwa Lipska is one of Europe's most compelling and important poets, but relatively little of her recent work has been translated into English. A Polish-English bilingual edition, Dear Ms. Schubert is the first complete collection of her remarkable poetic postcards addressed to "Ms. Schubert," a mysterious contemporary European everywoman.Written by a certain Mr. Schmetterling ("Mr. Butterfly"), these brief, intimate poems are by turns philosophical, political, and playfully erotic. Combining subversive wit and surrealist imagery, they slowly reveal the contours of a shared secret life played out against a turbulent historical backdrop-a relationship that strikes a precarious balance between deep cultural skepticism and authentic love.Featuring the original Polish text and the English translation on facing pages, Dear Ms. Schubert is a highly original and appealing book from a poet who richly deserves a wide English-language readership
Keywords: POETRY / European / General; Anthologie